Picosecond X-ray diffraction studies of shocked single crystals - art. no. 62610T - Wark, J; Belak, J; Collins, G; Colvin, J; Davies, H; Duchaineau, M; Eggert, J; Germann, T; Hawreliak, J; Higginbotham, A; Holian, B; Kadau, K; et al. (2006)
The past few years have seen a rapid growth in the development and exploitation of X-ray diffraction on ultra-fast time-scales. One area of physics which has benefited particularly from these advances is the the field of shock-waves. Whilst it has been known for many years that crystalline matter, subjected to uniaxial shock compression, can undergo plastic deformation and, for certain materials, polymorphic phase transformations, it has hitherto not been possible to observe the rearrangement of the atoms on the pertinent timescales. We have used laser-plasma generated X-rays to study how single crystals of metals (copper and iron) react to uniaxial shock compression, and observed rapid plastic flow (in the case of copper), and directly observed the famous alpha-epsilon transition in Iron. These studies have been complemented by large-scale multi-million atom molecular dynamics simulations, yielding significant information on the underlying physics.